The effectiveness of prescribed recreation activity in decreasing biochemical stress and improving mood in alcoholic patients - Russoniello, PhD, LRT/CTRS, LPC, Carmen (American Journal of Recreation Therapy, 2008)
The purpose of this controlled study was to determine whether prescribed recreation activity (RA) could decrease stress and improve mood. The study involved 20 male and female participants who were in alcohol rehabilitation. Ten participants served as matched controls. Treatment consisted of three groups of RAs classified according to physical intensity or the amount of oxygen required to perform them. Prescribed RAs (RXA) lasted 20 minutes and included three intensity levels. Biochemical analyses were coupled with psychological changes to test the study hypothesis. Results of the study indicated that participation in the RXAs reduced depression in the experimental group when compared with the control. Overall mood as well as its subcomponents, anger, tension, depression, fatigue, and vigor scores improved after both the low intensity (RXA1) and moderate intensity (RXA2) interventions. RXA1 and RXA2 interventions also produced statistically significant reductions in cortisol, a biochemical marker of stress. It is, therefore, concluded that prescribed RAs can produce biochemical and psychological changes consistent with decreased stress and improved mood. The ability to evoke positive physiological and psychological changes by more natural and less addicting behaviors provides rationale for this type of intervention as a potential complementary and alternative medicine. The findings of this study underscore the importance of recreational therapy in the treatment of alcoholism and other stress-related medical disorders.